PENGARUH LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA GURU SMP NEGERI 3 WALENRANG KABUPATEN LUWU - Lusindawati, Lusindawati; Nengsi, Nengsi; Nugrah, Yuda Satria; Baso, Nurfatimah Azzahra; Gustanti, Tri (Universitas Ichsan Sidenreng Rappang, 2025)
The purpose of this study was to analyze the influence of the work environment and leadership style on the performance of teachers at SMP Negeri 3 Walenrang, Luwu Regency. The data used were derived from primary and secondary data. Primary data were obtained through questionnaires distributed to teachers at SMP Negeri 3 Walenrang, while secondary data were obtained through various literature reviews. The study involved 21 teachers, using a saturated sampling method. The analysis tool used was multiple linear regression. The results showed that, based on the perceptions of SMP Negeri 3 Walenrang teachers, the work environment at SMP Negeri 3 Walenrang, Luwu Regency was good, with the highest average score for the relationship with colleagues indicator of 4.81. Meanwhile, leadership style at SMP Negeri 3 Walenrang, Luwu Regency was quite good, with the highest average score for the SIFTA indicator of 4.24. Based on the results of the multiple linear regression analysis, the work environment and leadership style had a significant effect on teacher performance, as evidenced by a significance value of 0.001 and a coefficient of determination of 52.4%. The work environment has a positive and significant effect on teacher performance at SMP Negeri 3 Walenrang, Luwu Regency. Leadership style has a positive and significant effect on teacher performance at SMP Negeri 3 Walenrang, Luwu Regency.